Concentrated Electrolyte for High‐Performance Ca‐Ion Battery Based on Organic Anode and Graphite Cathode. Issue 14 (11th February 2022) - Li, Jin; Han, Chengjun; Ou, Xuewu; Tang, Yongbing
Abstract: Due to the large abundance, low redox potential, and multivalent properties of calcium (Ca), Ca‐ion batteries (CIBs) show promising prospects for energy storage applications. However, current research on CIBs faces the challenges of unsatisfactory cycling stability and capacity, mainly restricted by the lack of suitable electrolytes and electrode materials. Herein, we firstly developed a 3.5 m concentrated electrolyte with a calcium bis(fluorosulfonyl)imide (Ca(FSI)2 ) salt dissolved in carbonate solvents. This electrolyte significantly improved the intercalation capacity for anions in the graphite cathode and contributed to the reversible insertion of Ca 2+ in the organic anode. By combining this concentrated electrolyte with the low‐cost and environmentally friendly graphite cathode and organic anode, the assembled Ca‐based dual‐ion battery (Ca‐DIB) exhibits 75.4 mAh g −1 specific discharge capacity at 100 mA g −1 and 84.7 % capacity retention over 350 cycles, among the best results known for CIBs. Abstract : Ca‐ion battery: Ascribed to the improved anion intercalation performance in the graphite cathode and reversible Ca 2+ insertion in the organic anode, by combining a 3.5 m concentrated Ca‐ion electrolyte with the low‐cost and environmentally friendly graphite cathode and organic anode, the proof‐of‐concept Ca‐based dual‐ion battery exhibits 75.4 mAh g −1 specific discharge capacity and 84.7 % capacity retention over 350 cycles, among the best results for Ca‐ion batteries.